Encyclopedia of medical immunology : allergic diseases - Rose, Noel R.; Ledford, Dennis K.; Lockey, Richard F.; Mackay, Ian R. (Springer New York, 2014)
Volume Allergic Diseases is a comprehensive, multi-authored reference work, offering a broad appeal to microbiologists, immunologists, and infectious disease specialists. The volume explores all aspects of allergic diseases, body systems and vaccines. Emphasis is placed on genetics, physiology, metabolism, pathogenesis, and applied microbiology. Under the leadership of some of the most world renowned names in the field, the encyclopedia brings together an outstanding collection of contributions by top scientists in a variety of fields. The entries are listed alphabetically and provide full references. The volume covers the following topics: • Food Allergy and gastrointestinal Allergic Diseases • Insect Allergy • Allergy Diagnosis and Testing • Allergy Treatment: Pharmacotherapy • Asthma and Other Allergic Lower Respiratory Disease • Biology of IgE, Mast Cells and Eosinophils • Specific Allergens Causing Human Disease • Atopic Dermatitis, Urticaria and Dermatologic Allergy • Allergy Treatment: Immunotherapy, Immunomodulator Therapy and Allergen Avoidance